Barriers to Physical Assessment: Registered Nurses in Mainland China. (January 2020) - Shi, Guang; He, Guan-Fei; Zhang, Li-Li; Morrow, Mary R.; Zhao, Yang
The authors focus on discussing the barriers in the use of physical assessment skills by RNs (Registered Nurses) in mainland China. This study was a multicenter, cross-sectional survey conducted in 6 cities with 1, 115 RNs in mainland China. The results indicated that 15.36% of the skills were used regularly, where general and skin condition assessment skills are used most frequently. Lack of training and a unified documentation form were the top two barriers RNs faced. In conclusion, RNs are not performing assessment skills with required proficiency in mainland China and still need managerial attention in continuing education.